quality of broiler fed diet supplemented by garlic meal and white turmeric meal - Dono, Nanung Danar (Indonesian Journal of Animal and Veterinary Sciences, 2010)
This research was done within 42 days to investigate the effect of diet supplemented by garlic (Allium sativum) and white turmeric (Curcuma xanthorrhiza Roxb) meals on physical and chemical quality of broiler meat. The number of 90 broiler DOC were used in this study.Â  They were randomly allocated into 18 unit of cages. During the study, the chicken were given 6 feeding treatments, i.e.: R-0 (98.0% base diet + 2.0% filler; as control diet), RB-1 (98.0% base diet + 1.0% garlic meal + 1.0% filler), RB-2 (98.0% base diet + 2.0% garlic meal), RT-1 (98.0% base diet + 1.0% white turmeric meal + 1.0% filler), RT-2 (98.0% base diet + 2.0% white turmeric meal), and RB1T1 (98.0% base diet + 1.0% garlic meal + 1.0% white turmeric meal). The base diet was composed of: yellow corn, soybean meal, fish meal, rice polishing meal, sorghum, poultry meat meal, mineral mix, and was design to contain 17.5% crude protein and metabolizable energy 2,900 kcal/kg. Variables observed were:Â  physical appearance (slaughter weight, non-feather weight, carcass weight), physical quality (pH, water holding capacity, cooking lose, tenderness), and cholesterol content (breast meat and blood cholesterol). All data were statistically analyzed by the Oneway of ANOVA and followed by the DMRT for significant results. Results showed that 1.0 - 2.0% garlic meal and 1.0 - 2.0% white turmeric meal supplementation reduced: breast meat cholesterol (P < 0.05), cooking lose (P < 0.05), and increased: pH (P < 0.01), and water holding capacity (P < 0.01) and improved tenderness (P < 0.05). Supplementation of 2% garlic meal and white turmeric meal didnât affect slaughter weight, non-feather weight, carcass weight, nor blood cholesterol. Key Kords: Physical And Chemical Quality, Broilerâs Meat, Garlic, White Turmeric